Multicentric infantile myofibromatosis with extensive visceral involvement in a newborn: case report - Rossella Vitale; Manuela Capozza; Antonia Filannino; Michele Quercia; Chiara Novielli; Grazia Calderoni; Francesco De Leonardis; Nicola Santoro; Stefania Martino; Nicoletta Resta; Nicola Laforgia (Italian Journal of Pediatrics)
Abstract Background Infantile myofibromatosis, a rare soft tissue neoplasm that may present at birth or in early infancy, is the most common fibrous tumor of infancy and early childhood. Diagnosis could be challenging due to different clinical presentation. Very few cases are detected prenatally and visceral involvement is extremely rare. Case presentation We present a case of Disseminated Infantile Myofibromatosis with challenging prenatal ultrasound and misleading clinical presentation. Diagnosis was very difficult and confirmed by pathology results obtained after birth. Conclusions Visceral involvement constitutes a specific unfavorable prognostic factor but a watchful waiting approach would always be appropriate, since spontaneous regression and a favourable evolution are possible and age-related chemotherapy severe side effects and long-term sequelae are matter of concern.